2013
DOI: 10.1136/jramc-2013-000048
|View full text |Cite
|
Sign up to set email alerts
|

From IEDs to AIDS? Detection of HIV in human corpses by rapid screening tests after suspected intentional transmission in terrorist attacks

Abstract: Rapid HIV testing from the remains of dead terrorists in the deployed military environment is possible. Samples should be acquired quickly, basic sample preparation is advisable and consequent decisions concerning postexposure prophylaxis should take into account the diagnostic gap in early infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Several studies (Padley et al ; Gubbe et al ; Meyer et al ) praised the ability of NAT to reliably detect HIV in post‐mortem samples; however, some studies reported contrasting results (Essary et al ; Strong et al ; Eriksen et al ; Frickmann et al ; Greenwald et al ). Eriksen et al () compared ante‐mortem and post‐mortem results and NAT gave false negative results in 50.0% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Padley et al ; Gubbe et al ; Meyer et al ) praised the ability of NAT to reliably detect HIV in post‐mortem samples; however, some studies reported contrasting results (Essary et al ; Strong et al ; Eriksen et al ; Frickmann et al ; Greenwald et al ). Eriksen et al () compared ante‐mortem and post‐mortem results and NAT gave false negative results in 50.0% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, Greenwald et al () compared EIA and NAT from individuals with a known history of HIV; NAT only detected HIV in 50.0% of the samples, while EIA detected HIV in 97.9%. Frickmann et al () found that NAT amplification was inhibited by post‐mortem serum, and the RNA copy number was diverse. In contrast, Strong et al () stated that NAT could reliably detected HIV in post‐mortem samples; however, reliable results were only obtained after a 1:5 dilution of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Humanitarian aid missions in conflict areas with a high HCV burden are associated with an increased risk. In asymmetric military conflicts, there is the additional jeopardy of infection due to ballistic transmission via bone fragment implantation during suicide bombing 5. For example, in Afghanistan, HCV seroprevalence of 36.6% among injecting drug users11 provides an easily accessible source for the self-inoculation of potential suicide assassins with fresh, replicative virus-containing blood.…”
Section: Discussionmentioning
confidence: 99%
“…The material was subsequently transferred into labelled, empty 10 mL test tubes (Harre Co., Hannover, Germany) 4 5…”
Section: Methodsmentioning
confidence: 99%
“…Aware of their military inferiority in logistics and firepower compared with regular troops, such irregular forces might try to partially compensate for this disadvantage by nefarious and internationally proscribed tactics of warfare. We have recently discussed the practicality of amplifying the effects of suicide bombing by the transmission of blood-borne viruses 1. Medical services must be prepared to cope with the physical and psychological consequences of irregular attacks targeting any of the potential weaknesses of deployed troops.…”
Section: Introductionmentioning
confidence: 99%